A new system to study directional volatile-mediated interactions reveals the ability of fungi to specifically react to other fungal volatiles - Bruisson, Sébastien; Alfiky, Alsayed; L'Haridon, Floriane; Weisskopf, Laure (Frontiers in Ecology and Evolution, 2023)
Microbes communicate with each other using a wide array of chemical compounds, amongst which volatile organic compounds (VOCs). Usually such volatile-mediated interactions are studied by growing two different microbes in a shared, confined environment and by subsequently collecting and analyzing the emitted VOCs by gas chromatography. This procedure has several drawbacks including artificial volatile overaccumulation and potential oxygen limitation, as well as the impossibility to assign a producer to the compounds newly emitted during the interaction. To address these challenges, we have developed a novel method to analyze volatile-mediated interactions allowing for sequential, unidirectional exposure of a receiving organism to the VOCs of an emitting organism. Using hermetically sealed boxes called “microcosms” connected to a pump generating a constant, unidirectional airflow, emitted VOCs are driven into and absorbed by a charcoal filter, avoiding artificial overaccumulation proof of concept, we used this newly developed experimental setup to characterize the reaction of a plant-growth promoting fungus (Trichoderma simmonsii) to the perception of VOCs emitted by two plant pathogens, Botrytis cinerea and Fusarium oxysporum. Our results show that the perception of both pathogens triggered important and pathogen-specific changes in the VOCs emitted by Trichoderma. Trichoderma’s volatilome modulation was overall stronger when exposed to the VOCs from Fusarium than to the VOCs from Botrytis, which correlated with increased siderophore production when co-incubated with this fungus. Our newly developed method will not only help to better understand volatile-mediated interactions in microbes, but also to identify new molecules of interest that are induced by VOC exposure, as well as the putative inducing signals themselves.